The Development of Qawā’idul I’lāl Teaching Materials by an Inductive Approach - Isnainiyah Isnainiyah; Mohamad Zaka Al Farisi; Asep Sopian (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2022)
TThe teaching and learning process of I'lāl (vocal deviation) in Islamic boarding schools generally uses the book of Qawā'idul I'lāl. However, the book of Qawā'idul I'lāl is still very simple and has several shortcomings as follows: (1) it only contains simple i'lāl rules, (2) there is no explanation of the rules, (3) there are only a few examples, and (4) there is no material for practice. Therefore, the researcher intends to develop Qawā'idul I'lāl teaching materials with an inductive approach accompanied by practice questions. On another note, this research aims to describe the product's feasibility and legibility. This study uses a research and development (R&D) design with a stage model developed by Borg & Gall. The study results indicate that, in the aspect of feasibility, this development product is declared feasible after it is tested by experts on the material and media’s morphology and visual communication design, with a result of 82.6%. Regarding readability, the product development is categorized as independent after conducting the gap test with 86.1% and the Fog Index formula with a value of 2.543. Therefore, the results of developing the Qawā'idul I'lāl book with an inductive approach have implications for the ideal product of teaching materials for I'lāl learning (vocal deviation), especially in the pesantren environment.